2017
DOI: 10.1103/physrevd.95.102001
|View full text |Cite
|
Sign up to set email alerts
|

3FGL J1924.8-1034: A spatially extended stable unidentified GeV source?

Abstract: Milky Way-like galaxies are predicted to host a very large number of dark matter subhalos. Some massive and nearby subhalos could generate detectable gamma-rays, appearing as unidentified, spatially-extended and stable gamma-ray sources. We search for such sources in the third Fermi Large Area Telescope source List (3FGL) and report the identification of a new candidate, 3FGL J1924.8-1034. With the Fermi-LAT Pass 8 data, we find that 3FGL J1924.8-1034 is spatiallyextended at a high confidence level of 5.4σ, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 70 publications
(91 reference statements)
2
18
1
Order By: Relevance
“…Using an analytical model of subhalo mass stripping that has been calibrated against numerical simulation results, combined with current limits on the DM annihilation cross section from known Milky Way dSphs, we estimated the gamma-ray flux and source size as a function of pre-infall halo mass for all eight Fermi-LAT sources. We concluded that our model rejects the possibility of a DM annihilation scenario for the two sources: 3FGL J2212.5+0703 (Bertoni et al 2016) and 3FGL J1924.8-1034 (Xia et al 2017) if the pre-infall DM halo mass is less than M 200 < 10 9 M at distance of d < 20 kpc, as constrained by our work. If the subhalo is farther away than 20 kpc, then its DM halo has to be larger than M 200 = 10 9 M .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Using an analytical model of subhalo mass stripping that has been calibrated against numerical simulation results, combined with current limits on the DM annihilation cross section from known Milky Way dSphs, we estimated the gamma-ray flux and source size as a function of pre-infall halo mass for all eight Fermi-LAT sources. We concluded that our model rejects the possibility of a DM annihilation scenario for the two sources: 3FGL J2212.5+0703 (Bertoni et al 2016) and 3FGL J1924.8-1034 (Xia et al 2017) if the pre-infall DM halo mass is less than M 200 < 10 9 M at distance of d < 20 kpc, as constrained by our work. If the subhalo is farther away than 20 kpc, then its DM halo has to be larger than M 200 = 10 9 M .…”
Section: Discussionsupporting
confidence: 54%
“…The differences come from the fact that small changes of internal profiles such as r s and ρ s (e.g., Peñarrubia et al 2010) have been taken into account for the former approach based on Bartels & Ando (2015) and Hiroshima et al (2018), but not in the latter. 1034 (circle; Xia et al 2017), the measured signals are incompatible with a DM annihilation interpretation, even for halos at the pre-infall halo mass upper bound of M 200 = 10 9 M . We note that recently Fermi- LAT Collaboration & Biteau (2018) reported that the gamma-ray signals from both 3FGL J2212.5+0703 and 3FGL J1924.8-1034 are better explained by two point sources rather than a single extended source.…”
Section: Dark Matter Interpretation Of the Fermi -Lat Unassociated Ementioning
confidence: 91%
“…We note that no source flagged as extended in the catalogs survived our cuts. In particular, the source 3FGL J2212.5+0703, which is marked as possible DM subhalo by [30], is rejected by its multiwavelength emission, and 3FGL J1924.8-1034, which is also marked as a possible extended DM subhalo by [88], is classified as an AGN by the machine-learning algorithms. Table 2 summarizes the expected efficiency, defined as the fraction of each filtering effect which is univocally applied (i.e., with no possibility of a false positive), and how we dealt in each case with the fact of not having 100% efficiency.…”
Section: Complex Regionsmentioning
confidence: 99%
“…For some subhalos which are too small to capture enough baryonic matter (i.e., M sub < 10 8 M ), the gamma-ray annihilation signals would be the only channel to observe them. Thus, it is supposed that some unassociated Fermi-LAT sources are potential DM subhalos [28][29][30][31][32][33][34][35][36], especially those spatially extended and with spectra compatible with DM signals [32,35,36].…”
Section: Searching For Counterparts Of the Weak Line-like Excessesmentioning
confidence: 99%